Non-resonant Raman scattering through a metal-insulator transition: an exact analysis of the Falicov-Kimball model - Freericks, J.K.; Devereaux, T.P. (Condensed Matter Physics, 2001)
For years, theories for Raman scattering have been confined to either the insulating or fully metallic state. While much can be learned by focusing attention on the metal or insulator, recent experimental work on the cuprate systems points to the desirability of formulating a theory for Raman response which takes one through a quantum critical point – the metalinsulator transition. Using the Falicov-Kimball model as a canonical model of a MIT, we employ dynamical mean-field theory to construct an exact theory for non-resonant Raman scattering. In particular we examine the formation of charge transfer peaks and pseudogaps as well as the low-energy dynamics. The results are qualitatively compared to the experimental B₁g Raman spectra in the cuprates, which probes the hot quasiparticles along the Brillouin zone axes. The results shed important information on normal state electronic transport and the pseudo-gap in the cuprates. Упродовж років теорія комбінаційного розсіяння (КР) обмежувалася розглядом або ізоляторів або суто металічного стану. Хоча можна багато довідатися, зосередивши увагу тільки на металах чи ізоляторах, останні експериментальні роботи з купратних систем вказують на бажаність формулювання теорії раманівського відгуку, яке придатне при проходженні через квантову критичну точку - перехід метал-ізолятор (ПМІ). Використовуючи модель Фалікова-Кімбала як канонічну модель ПМІ, ми застосовуємо теорію динамічного середнього поля для побудови точної теорії нерезонансного КР. Зокрема, ми розглядаємо утворення піків, зумовлених переносом заряду, та псевдощілин, а також низькоенергетичну динаміку. Результати якісно зіставимі з експериментальними B₁g спектрами КР у купратах, в яких фіксують “гарячі” квазічастинки вздовж осей зони Брілюена. Результати дають важливу інформацію про електронний транспорт у нормальному стані та псевдощілину в купратах.